Researching relations between hearing Sign Language interpreters and their deaf clients: Methodological considerations on empirical data collection with prelingually Deaf participants - Maaß, Laura Marie (Linguistik Online, 2022)
The present paper discusses necessary adaptations in research methodology to include Deaf Sign Language users in a survey on Sign Language interpreting. Prelingually Deaf Sign Language users have, on average, lower literacy levels than their hearing counterparts. Many of them disfavour reading and writing texts and prefer to be addressed with, and communicate in Sign Language. The present paper reports on a survey among hearing Sign Language interpreters and Deaf Sign Language users that included qualitative expert interviews and a questionnaire with multiple choice as well as free text answers. In total, the questionnaire was processed by 771 participants, 325 of whom are hearing Sign Language interpreters and 446 Deaf Sign Language users. The paper reports on how the data was collected among the Deaf participants including the use of Sign Language and Sign Language oriented Easy Language Plus in order to meet their communicative preferences. The paper is a contribution to the current efforts in Accessible Communication research to adapt methodology according to the participant’s communicative needs.